EDUKASI PENCEGAHAN PENYAKIT DIABETES MELLITUS PADA MASYARAKAT KELURAHAN BUJEL KEDIRI: DIABETES MELLITUS PREVENTION EDUCATION IN BUJEL KEDIRI COMMUNITY - Laili, Nur Fahma; Sukmawati, Datin An'Nnisa; Probosiwi, Neni (Jurnal Abdi Masyarakat, 2023)
Diabetes mellitus is a disease whose prevalence continues to increase. The low level of public knowledge about a healthy lifestyle is one of the reasons for the increase in the incidence of the disease. One of the efforts made is to prevent diabetes mellitus by adopting healthy lifestyle habits. The role of family and health workers is very important in the success of therapeutic management.So it is necessary to conduct education on the prevention and treatment of diabetes mellitus in the Bujel village. In addition to education, this service activity includes checking blood sugar levels so that residents of the Bujel sub-district take preventive measures early on. The service method is carried out including the pest test activity, then an educational explanation on the prevention of diabetes mellitus is carried out, then a post test. Selain itu juga dilakukan pemeriksaan kadar kadar gula darah. Results of checking blood sugar levels There were 18 people with blood sugar levels > 200 mg/dl, The results of community service activities obtained an average value before education was 65, while the average value after education is 75. This shows that there has been an increase in participants' understanding of knowledge between before and after education.